From scientific article to press release to media coverage: advocating alcohol abstinence and democratising risk in a story about alcohol and pregnancy. (17th August 2016) - Lee, Ellie; Sutton, Robbie M.; Hartley, Bonny L.
Abstract : In this article, we follow the approach taken by Riesch and Spiegalhalter in "Careless pork costs lives': Risk stories from science to press release to media' published in this journal, and offer an assessment of one example of a 'risk story'. Using content and thematic qualitative analysis, we consider how the findings of an article 'Fetal Alcohol Exposure and IQ at Age 8: Evidence from a Population-Based Birth-Cohort Study' were framed in the article itself, the associated press release, and the subsequent extensive media coverage. We contextualise this consideration of a risk story by discussing a body of work that critically engages with the development and global proliferation of efforts to advocate for alcohol abstinence to pregnant (and pre-pregnant) women. This work considers the 'democratisation' of risk, a term used to draw attention to the expansion of the definition of the problem of drinking in pregnancy to include any drinking and all women. We show here how this risk story contributed a new dimension to the democratisation of risk through claims that were made about uncertainty and certainty. A central argument we make concerns the contribution of the researchers themselves (not just lobby groups or journalists) to this outcome. We conclude that the democratisation of risk was advanced in this case not simply through journalists exaggerating and misrepresenting research findings, but that communication to the press and the initial interpretation of findings played their part. We suggest that this risk story raises concerns about the accuracy of reporting of research findings, and about the communication of unwarrantedly worrying messages to pregnant women about drinking alcohol.